Better pathways to success? – A study of foundation studies alumni. Issue 2 (1st October 2018) - Teo, Ian; Chang, Shanton
Foundation studies (or pathways) programmes (FSPs) seek to prepare international students for their transition into university by providing bridging courses to meet their academic, sociocultural and personal needs. The growth of such programmes over the previous decade has boomed to over 1000 English-medium providers worldwide and has been valued at $1.4 billion with no indication of slowing down. While these programmes serve an instrumental purpose in terms of providing international students with a pathway into university, it has become clear that these students seek more than just a qualification by the end of their sojourn, and value also the quality of their broader relationships, preparation and participation at university. For more than 25 years, Trinity College Foundation Studies (TCFS) in Melbourne has served to prepare a wide-range of international students for their higher education (HE) studies. The present study will report on quantitative and qualitative data derived from TCFS alumni who were surveyed at the start of 2017. In particular, two branches of alumni-related expectations and experiences will be addressed. First, the types of extra-curricula activities respondents reflected upon as being important for their broader welfare or well-being while enrolled as foundation students will be discussed. Second, findings involving the types of support they sought during and after university, and the ways in which they wished to reconnect with TCFS will be described. Implications and recommendations relating to the aforementioned data will subsequently be presented.